EVALUASI DAMPAK KEBIJAKAN PEMBANGUNAN PLTU TERHADAP KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DESA KARANGGENENG KECAMATAN KANDEMAN KABUPATEN BATANG - Dewi Prabandari; Aloysius Rengga (Journal of Public Policy and Management Review, 2018)
PLTU Batang is a steam power plant built in Batang Regency which is expected to meet the need national electricity in Java and Bali Regions. The PLTU is located in three villages namely Ujungnegoro, Karanggeneng, and Ponowareng, near Ujungnegoro Sea. Among the three villages, Karanggeneng get the biggest impact due to the majority of its people suffered from the effect of PLTU development. The aim of this research is to evaluate the policy effects of PLTU development towards the social life of Karanggeneng Village people. This research used a descriptive qualitative method. The used data collection technique are interviews, observations, and documentation. Evaluation on the effects of PLTU Batang used the policy dimensions model by Thomas R. Dye. The results of the research indicates that the existence of PLTU Batang gives an effect to Karanggeneng Village people they were forced to sell their lands. The local people’s future is also affected because the transfer of land function sresults in people losing their livelihoods. The PLTU policy has an effect on the current and future conditions that are increasing unemployment and poverty in Karanggeneng Village. However, the form of responsibility of PT PBI is the establishment of KUB for the affected society. It is recommended that the development of PLTU Batang should pay more attention on the people’s social economic condition.